2020
DOI: 10.1002/cne.25054
|View full text |Cite
|
Sign up to set email alerts
|

Retinal horizontal cells of goldfish (Carassius auratus) display subtype‐specific differences in spontaneous action potentials in situ

Abstract: Horizontal cells (HCs) are neurons of the outer retina, which provide inhibitory feedback onto photoreceptors and contribute to image processing. HCs in teleosts are classified into four subtypes (H1-H4), each having different roles: H1-H3 feed back onto different sets of cones, H4 feed back onto rods, and only H1 store and release the inhibitory neurotransmitter, γ-aminobutyric acid (GABA). Dissociated HCs exhibit spontaneous Ca 2+-based action potentials (APs), yet it is unclear if APs occur in situ, or if a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…1A-D) based on morphological description from previous studies (Dowling et al, 1985;Tachibana, 1981;Country et al, 2021) and observed no apparent differences in morphology between summer and winter. Plotting the distribution of the ratio of dendritic field area to soma area provided an estimate of the subtypes present in the dissociation (Country et al, 2021). Calculation and plotting of the rd/s values of 80 neurons showed that the distribution of cells isolated during the summer and winter were similar, with median rd/s values of 7.2 and 6.2, respectively (Fig.…”
Section: Cell Morphology and Membrane Surface Area Were Consistent Be...mentioning
confidence: 84%
See 4 more Smart Citations
“…1A-D) based on morphological description from previous studies (Dowling et al, 1985;Tachibana, 1981;Country et al, 2021) and observed no apparent differences in morphology between summer and winter. Plotting the distribution of the ratio of dendritic field area to soma area provided an estimate of the subtypes present in the dissociation (Country et al, 2021). Calculation and plotting of the rd/s values of 80 neurons showed that the distribution of cells isolated during the summer and winter were similar, with median rd/s values of 7.2 and 6.2, respectively (Fig.…”
Section: Cell Morphology and Membrane Surface Area Were Consistent Be...mentioning
confidence: 84%
“…We identified all subtypes of horizontal cells (Fig. 1A-D) based on morphological description from previous studies (Dowling et al, 1985;Tachibana, 1981;Country et al, 2021) and observed no apparent differences in morphology between summer and winter. Plotting the distribution of the ratio of dendritic field area to soma area provided an estimate of the subtypes present in the dissociation (Country et al, 2021).…”
Section: Cell Morphology and Membrane Surface Area Were Consistent Be...mentioning
confidence: 84%
See 3 more Smart Citations